Recovery of tigers in India: Critical introspection and potential lessons. Issue 2 (25th February 2021) - Jhala, Yadvendradev; Gopal, Rajesh; Mathur, Vaibhav; Ghosh, Prodipto; Negi, Himmat Singh; Narain, Sunita; Yadav, Satya Prakash; Malik, Amit; Garawad, Rajendra; Qureshi, Qamar
Abstract: In a world where biodiversity is on the decline, examples of conservation success especially of large carnivores are of interest to policy makers and conservation practitioners. Herein, we elucidate the conservation actions that have been responsible for the recovery of tigers and their ecosystems in India; a feat many range countries are struggling to achieve. Demand‐driven poaching resulted in extinctions at two prestigious Tiger Reserves. India's Prime Minister constituted a Tiger Task Force that led to the formation of the National Tiger Conservation Authority, the Wildlife Crime Control Bureau, scientific monitoring of tiger populations and incentivized voluntary relocation of human settlements from tiger reserves. Tiger Conservation Plans, cognizant of constraints imposed by small reserves embedded in human land uses, aimed to create source populations within tiger reserves with corridor links between sources and to sink habitats. Metapopulation management enhanced occupancy and long‐term viability of tiger populations. Tiger Protection Force and technology like MSTrIPES, E‐eye and drones effectively reduced poaching. Community support was attempted through profit sharing, mitigating human–tiger conflict with a fast, fair and transparent compensation process and removal of problem tigers. Reintroduction and reinforcement of tigers and prey assisted natural recovery. Political will ensured resources. Tigers were monitored using Spatially Explicit Capture–Recapture with camera traps and ecological covariates. In 2018–2019 from 381, 000 km 2 of tiger habitat, 89, 000 km 2 was occupied. Currently, 50 tiger reserves cover 72, 750 km 2 and harbour 65% of India's 3, 000 tigers. Tiger reserves are managed with an annual investment of 1, 000 USD/km 2 with one staff per 6.5 km 2 . Tiger reserves were regularly evaluated for Management Effectiveness. Tiger reserves were valued to have benefit flows between 76, 900 and 292, 300 US km −2 year −1 . In the Anthropocene it is unlikely that tigers will survive without targeted conservation investments. Political commitment and resources can become available for conservation when people and tigers benefit simultaneously. Conscious balance by governments between development for rapid economic prosperity and long‐term ecological security will ensure that wild tigers and their intact ecosystems will survive for future generations. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. सार: एक ऐसी दुनिया में जहाँ जैव विविधता घट रही हैं, विशेष रूप से बड़े मांसाहारी जानवरों के संरक्षण की सफलता के उदाहरण नीति निर्माता और संरक्षण कर्ताओं के लिए रूचि रखते है| इस लेख में, हम उन संरक्षण कार्यों को स्पष्ट कर रहे हैं जो भारत में बाघों और उनकी परिस्थिति तंत्र की बहाली के लिए जिम्मेदार हैं| यह एक ऐसी उपलब्धी है जो बाघों के इलाके वाले देश हांसिल करने के लिए संघर्ष कर रहे हैं| हाल ही में वैश्विक मांग से प्रेरित अवैध शिकार के कारण दो बाघ संरक्षण क्षेत्रों से बाघ विलुप्तह हो गए, इस कारण भारत के प्रधान मंत्री ने एक बाघ कार्यकारणी बल का घट्न किया| इस कार्यकारणी बल ने राष्ट्र बाघ संरक्षण प्राधिकरण, वन्य जीव अपराध नियंत्रण ब्यूरो, बाघों की आबादी की वैज्ञानिक निगरानी और बाघों के संरक्षण क्षेत्रों से मानव बस्तियों के स्वेच्छिक पुनर्वास को प्रोत्साहित करने का कार्य किया| बाघ संरक्षण योजना इसको ध्यान में रख कर बनाई गयी, के बाघ की ज़्यादातर जनसंख्या छोटे क्षेत्रों में बिखरी हुई है| जिसके लिए जन संख्या क्षेत्रों को गलियारों से जोड़ना जरूरी है| मेटापापुलेशन प्रबंधन को अपनाने से बाघों के आबादी को संरक्षण क्षेत्रों में अधिक समय तक जीवित रहने लायक बनाया| बाघ संरक्षण बल और तकनीकी का उपयोग, जैसे, एम् स्ट्राइप्स, इ‐ऑय, और ड्रोन्स ने प्रभावी रूप से अवैध शिकार को काम करने में मदद की| लोगों से सामुदायिक समर्थन का प्रयास इस प्रकार किया गया, जैसे लोगों को संरक्षण से होने वाले लाभ में हिस्से दारी हो, मुआवजा निष्पक्ष और पारदर्शी हो, मानव बाघ संघर्ष को काम करने के उपाय कारगर हो| बाघों और चौपायों के पुनर्स्थापन और बचाव से प्राकृतिक बहाली हुई| राजनीतिक सुनिश्चिता ने संसाधन मुहैय्या कराने में मदद की| बाघों की जनसंख्या कैमेरा ट्राप द्वारा स्पेश्यली‐ एक्सप्लीसिट‐ कैप्चर‐रीकैप्चर पद्धती से एवं पारस्थितिक सहसमानयोजकों का इस्तमाल कर की गयी| २०१८‐१९ में ३८१, ००० वर्ग की|मी| वन क्षेत्र में कार्य किया गया, जिसमें ५० बाघ संरक्षण क्षेत्रों का ७२, २१८ वर्ग की.मी. भी शामिल है| इन बाघ संरक्षण क्षेत्रों में देश के ३, ००० बाघों में से ६५% इन क्षेत्रों में पाए जाते है| बाघ संरक्षण क्षेत्रों के प्रभंधन में १००० यू यस / की.मी. का व्यय प्रति वर्ष होता है एवं प्रति ६0.५ वर्ग की.मी. में एक सरकारी कर्मचारी इन क्षेत्रों की देखभाल करता है| बाघ संरक्षण क्षेत्रों का नियमित रूप से प्रभंधन मूल्यांकन उनकी प्रभावशीलता मापने के लिए किया जाता है| बाघ संरक्षण क्षेत्रों से लगभग ७६, ९०० से २९२, ३०० यू यस प्रति वर्ग की.मी. का फायदा समाज को होता है| आज के मानव आधारित युग में यह संभावना नहीं है की लक्षित संरक्षण निवेश के बिना बाघ जीवित रहेंगे| राजनीतीक प्रतिभद्धता और सनसाधन संरक्षण तभी उपलब्ध हो सकते है जब लोग और बाघ एक साथ लाभवंतित हो| आर्थिक समृद्धि और दीर्घकालिक परिस्थितिक सुरक्षा के विकास के लिए, सरकारों द्वारा संतुलन सुनिश्चित करेगा की जंगली बाघ और उनके परिस्थितिक तंत्र भविष्य की पीढ़ी के लिए जीवित रहेंगे|